Analisis of Business Feasibility and Exchange Value of Madidihang Tuna Fisherman in Dufa-Dufa Village, Ternate City - Muksin, Darmiyati; Drakel, Julfita U Ali; Karman, Amirul (Agrikan Jurnal Agribisnis Perikanan, 2022)
The purpose of this research is to analyze the economic aspect and to analyze the trade value of yellowfin tuna hand line fishermen. The research was conducted in the Dufa-Dufa Village, Ternate City in September. Field data collection for 1 week, from 1 – 7 September 2022. The research method used is the survey method. The average profit value based on actual data analysis is Rp. 28,779,833.33/year, using the sensitivity of scenario 1 of Rp. 30,356,718.75/year, and scenario 2 is Rp. 104,361,187.50/year. The average value of B/C ratio of actual data is 3.80, the sensitivity of scenario 1 is 5.64 and scenario 2 is 8.90. The average actual data IRR value is 72.61%, the sensitivity of scenario 1 is 100.24%, and scenario 2 is 145.25%. The average BEP value of actual data is Rp. 219,787,499.96, the sensitivity of scenarios 1 and 2 has the same BEP value of Rp. 296,374,999.97. The average PP value of actual data is 1.84 years, the sensitivity of scenario 1 is 2.27 and scenario 2 is 0.76 years. The fishermen's exchange rate (NTN) for yellowfin tuna fishing line during the period September 2022 – October 2022, from total family income as well as from capture fisheries business income, the value is above one..